PENERAPAN METODE DEMONSTRASI DAN PENUGASAN BERBASIS GOOGLE FORMULIR BERBANTUAN MEDIA PEMBELAJARAN VPAMS-PPT UNTUK MENINGKATKAN HASIL BELAJAR MATERI SENAM LANTAI PESERTA DIDIK KELAS VIII D MTs NEGERI 3 BANTUL - Tri Iwandana, Dody; Stiyapranomo, Dwi Arif (Faculty of Sport and Health Sciences, 2022)
This study aims to improve the process and learning outcomes of students in absorbing motion material for floor gymnastics activities with the application of demonstration and assignment methods at MTsN 3 Bantul. This type of research is a type of classroom action research. The subjects of this study were students of class VIII D MTsN 3 Bantul, totaling 30 children. The results showed that the application of the Google form-based demonstration and assignment method with the help of VPAMS-ppt learning media to improve learning outcomes of floor gymnastics for class VIII D Students of MTs Negeri 3 Bantul. Based on the results of data analysis at the end of the cycle, the graduation achievement rate in the knowledge assessment aspect is 80% while the graduation achievement in the skills aspect reaches 83.33% with a KKM score of 75. Thus, it can be concluded that the implementation of demonstration methods and assignments based on google forms assisted media VPAMS-ppt learning to improve learning outcomes of floor gymnastics for Class VIII D MTs Negeri 3 Bantul students was successful.